Sustainable Energy System Planning : Renewable Resource Dynamics - Spittler, Nathalie (CCSD, 2019)
A holistic understanding of the underlying dynamics of sustainable energy system development and its effects on socio-economic and environmental aspects, in different national contexts, is necessary for improved decision making with regards to sustainable energy system planning. In this thesis, systems thinking approach (i.e. causal loop diagrams) is first applied to explore the general dynamics of sustainable energy system development, including the feedbacks and leverages that promote or prevent sustainable energy system development. Second, the emerging energy paradigm (i.e. sustainable energy) and questions related to the challenges arising from it are defined. An extensive model review, which assesses to what extent existing energy system models can provide answers or address the questions arising from the current energy paradigm is presented. This helps identify strengths and weaknesses of energy system models. One of the identified gaps in current energy system models is the simplified representation of the physical realities of renewable resources. This is particularly the case for geothermal resources. Therefore, the third step involves the development of a system dynamics model that captures the behaviour of geothermal resources when they are utilised for electricity production. This geothermal resource dynamics model can capture the effects of geothermal resource dynamics on capacity expansion, resource availability, production levels as well as development and unit production costs at a national systems level. Based on the findings that estimated costs significantly increase when geothermal resource dynamics are considered, while resource availability is also affected, the developed geothermal resource dynamics model assesses the effects of geothermal resource dynamics in Iceland and Kenya. For Kenya, an electricity system model that includes the dynamics of geothermal and hydropower is built. This model explores the effects of renewable resource dynamics (i.e. geothermal and hydropower) on ...